mRNA expression of CYP17A1, CYP11A1, CYP19A1, HSD3B1 and AKR1C2 in metastatic and non-metastatic prostate cancer patients - Indrawarman Soerohardjo; Muhammad Puteh Mauny; Alharsya Franklyn Ruckle; Ahmad Zulfan; Raden Danarto; Didik Setyo Heriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The progression of prostate cancer (PCa) mainly occurs caused by androgens. There is a linkbetween intratumoral steroidogenesis and castration-resistant prostate cancer. This studyaimed to determine the mRNA expression of various steroidogenic enzymes (CYP17A1,CYP11A1, CYP19A1, HSD3B1, and AKR1C2) in metastatic and non-metastatic prostatecancer patients. This study was conducted at the Anatomical Pathology Laboratory andUrologi Division, Department of Surgery, Faculty of Medicine, Public Health and Nursing,Universitas Gadjah Mada/Dr. Sardjito General Hospital, Yogyakarta from September-November 2017. Samples were taken from 30 paraffin blocks with adenocarcinoma ofprostate, stained with hematoxylin-eosin (HE) and then classified into metastatic and nonmetastaticgroups. Samples then underwent deparaffinization procedure and examinationof mRNA expression of CYP17A1, CYP11A1, CYP19A1, HSD3B1, AKR1C2 genes usingReal-Time PCR. The mean mRNA expressions of CYP11A1, CYP17A1, CYP19A1,HSD3B1, and AKR1C2 genes in the metastatic adenocarcinoma prostate group were 7.08,10.11, 3.94, 4.84 and 3.58, respectively. In the non-metastatic group, the mean mRNAexpressions of CYP11A1, CYP17A1, CYP19A1, HSD3B1, and AKR1C2 genes were 4.62,9.45, 3.46, 2.68 and 4.92, respectively. The mean of mRNA expression of CYP11A1,CYP17A1, CYP19A1, and HSD3B1 genes were higher in the metastatic group than nonmetastaticadenocarcinoma prostate group. However, it was not statistically significant(p>0.05). The highest mRNA expression of steroidogenic enzymes was the CYP17A1gene. In conclusion, the mRNA expressions of CYP17A1, CYP11A1, CYP19A1, HSD3B1were higher in the metastatic prostate cancer patients compared to that in non-metastaticprostate cancer patients but statistically not significant.